A Metasurface Based Gain Enhanced Dual Band Patch Antenna Using SRRs With Defected Ground Structure - Samantaray D.; Bhattacharyya S. (My University, 2025)
This study proposes a metasurface (MS) based high performance antenna in which the radiating patch is embedded with split ring resonators in its square slots. The slotted corner cut rectangular patch antenna with defected ground plane and the MS are placed together in the same plane. The designed prototype operates over dual frequencies with impedance bandwidths (S11 < −10 dB) of 4.02% and 28.24% at 9.20 and 11.65 GHz respectively. The antenna possesses a maximum return loss of 42 dB at 11.65 GHz over 11.23–14.5 GHz band while the measured realized gain of 10.66 dBi has been obtained at 14.44 GHz. The antenna exhibits unidirectional far-field radiation characteristics and the radiation efficiency of 67% has been achieved at 14.44 GHz. The antenna prototype has been fabricated on FR4 dielectric substrate, having an electrical size of 1.16λ0 × 1.82λ0 × 0.06λ0, where λ0 is the free-space wavelength at 11.65 GHz. This makes the proposed antenna single-layer, broad impedance bandwidth, high gain and ease of fabrication in nature. The measured results are in good agreement with the simulated ones. The designed antenna can be applicable in defense and military, satellite communication, medical analysis for determination of radio waves and numerous communication fields. © 2021. American Geophysical Union. All Rights Reserved.